Formula for obtaining photo-crosslinking plastisol and method for photo-crosslinking plastisol
The photopolymerization reaction in polyvinyl chloride plastisol is carried out through ultraviolet crosslinking technology, which solves the problems of high energy costs and serious environmental pollution caused by high temperature and long-term processing in the existing methods, and achieves efficient crosslinking and curing of polymers, reducing process complexity.
Patent Information
- Application Number
- CN202411481163.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-28
AI Technical Summary
The existing polyvinyl chloride plastisol processing methods require high temperature and long-term processing, resulting in high energy costs, serious environmental pollution and complex processes.
UV cross-linking technology is adopted to achieve cross-linking and curing of polymers by adding specific photoinitiators, gelling agents and melt plasticizers to the polyvinyl chloride plastisol.
This method does not require high-temperature processing, and only ultraviolet light can achieve cross-linking and curing of polymers, reducing energy consumption and environmental pollution, and improving the simplicity and efficiency of the process.
Smart Images

Figure CN119529441A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a formula for converting polyvinyl chloride plastisol by photocrosslinking reaction, that is, obtaining polyvinyl chloride plastisol and forming polyvinyl chloride plastisol coating on the surface of substrate by ultraviolet light crosslinking. The present invention also relates to a method for photocrosslinking plastisol.
[0002] The invention can be actually applied to the production of advertising materials, plastic seals, wallpapers, artificial leather, inflatable castles and the like. Background Art
[0003] Polyvinyl chloride, also known as PVC, is a semi-crystalline homopolymer with a high elastic modulus. It is essential for the manufacture of flexible polyvinyl chloride products and can be used as an additive, such as plasticizer, stabilizer, dye, filler, lubricant and special additives such as flame retardants, antimicrobial agents, UV protectants and antistatic agents. Polyvinyl chloride plastisol is a suspension of polyvinyl chloride emulsion in plasticizer.
[0004] Copolymers are polymers that have a ring structure containing two or more monomers. Unlike copolymers, polymers that have only one monomer are usually called homopolymers. The main reason for obtaining copolymers is their special physical properties that are not possessed by homopolymers and mixtures containing simple monomers. In the present invention, copolymers are also called polyvinyl chloride raw materials, which have a polymer ring structure of vinyl acetate with acrylic acid or vinyl acetate polymer attached.
[0005] The constant K value for PVC resins is most commonly calculated using the Fickenchel formula, based on the commonly used dilute solution viscosity test, and is between 51 and 71. Plastisol resins are sometimes called dispersion resins or paste resins (primarily in Europe). Graft copolymers are another type of resin used in the production of vinyl thermoplastic elastomers and unplasticized flexible vinyl products or lightly plasticized flexible polyvinyl chloride with low extractables content.
[0006] The crystalline microdomains of plasticized PVC are distributed in the amorphous region, acting in a manner similar to the cross-linking in rubber to resist creep, compression and thermal deformation. The difference is that it is thermally reversible.
[0007] The vast majority of these crystals melt at processing temperatures and reform during the cooling of the molten plasticized PVC alloy. However, the behavior of crystal melting and recrystallization is very complex because PVC contains several different crystals that melt and reform at different temperatures. The process of these crystal melting and recrystallization is affected by the type of plasticizer. "Low-temperature" plasticizers, such as di-(2-ethylhexyl) adipate (DOA), mainly plasticize the non-crystalline regions of PVC, have little effect on the crystalline melting point, and require higher processing temperatures than fast-melting plasticizers or general-purpose plasticizers.
[0008] As is known, the process of producing polyvinyl chloride plastisol uses the following substrates.
[0009] Primary plasticizers are the main additives used in the plasticization process of PVC. This type of plasticizer can be divided into monomer plasticizers, polymer plasticizers, epoxy resin plasticizers and special flame retardant plasticizers, all of which are low-volatile liquids with polarity and other properties sufficient to make them compatible with PVC. Secondary plasticizers are low-volatile liquids. Their compatibility with PVC allows them to be used as part of the plasticizer system together with primary plasticizers. However, when used as the only plasticizer, they will migrate to the surface of the finished product.
[0010] Chlorinated paraffin is a common secondary plasticizer for PVC, which is used because of its low cost and lower flammability than most primary plasticizers.
[0011] There are many kinds of solid PVC elastomers, including compatible nitrile rubber, compatible polyurethane, compatible polyester fiber, ethylene oxide-carbon-vinyl acetate terpolymer and some polyacrylates. These solid materials are mainly used for thermoplastic PVC elastomer (TPE) blends and special PVC materials, some of which have low flammability and low smoke release.
[0012] The epoxy group molecules in epoxy resin plasticizers are derived from the epoxidation of olefin double bonds in the initial raw materials.
[0013] They are used as co-stabilizers together with appropriate amounts of mixed metal stabilizers and some new stabilizers. Epoxidized soybean oil (ESO) and epoxidized linseed oil (ELO) are the most commonly used epoxides.
[0014] Phosphate plasticizer - dipropylene glycol dibenzoate.
[0015] A portion of citrate plasticizers, such as acetyl tributyl citrate and butyryl tri-n-hexyl citrate.
[0016] There are also some mixed metal stabilizers, such as zinc compounds and mixed fatty acid salts.
[0017] Photoinitiators can be divided into two categories. The first type of photoinitiators undergo photodissociation upon absorption of radiation, generating free radical pairs. The second type of photoinitiators are binary systems, where an excited photoinitiator molecule reacts with another non-excited molecule, called a co-initiator, to generate the corresponding free radicals.
[0018] Furthermore, the results showed that chlorinated aromatic hydrocarbons facilitate photopolymerization.
[0019] Photopolymerization is the polymerization of low molecular weight molecules upon exposure to light. This applies to both direct double bond excitation and sensitization or clarification of photoactive compounds, a reaction also known as photoinitiation. Photoinitiated polymerization is the most common and versatile method and follows a classic free radical or cationic polymerization mechanism. In addition to initiators, monomers also participate in the reaction process. These monomers crosslink the expanding chain segments, promoting the formation of insoluble tough polymer materials. This combination of initiator, monomer, and crosslinker is often referred to as a "resin." To maximize photopolymerization, key challenges need to be overcome, such as oxygen inhibition, suitable light source, resin formation, initiator selection, and especially volume compression. Converting a liquid to a solid in a few seconds creates stress in the material that is dissipated by applying high temperatures for a long time during traditional thermal polymerization. Today, photopolymerization is widely used in adhesives, metal surface treatments, graphic and decorative coatings, medical devices, and even nail art.
[0020] There is also known free radical photopolymerization of plastic materials, which is a special form of free radical polymerization in which light is used to initiate polymerization. The main limitation of photoinduced polymerization is the limited penetration of light, which depends on the wavelength and spectral analysis of the light, but does not exceed a few millimeters. Since the polymerization reaction stops when the light source is removed, photopolymerization technology is only useful in thin film applications. Photochemical initiation is usually achieved by exposing a suitable photoinitiator to UV light. The absorption of light (photons) converts the absorbing molecule (PI) into an activated form, which rapidly dissociates into free radicals or ions (I). These molecular fragments initiate polymerization and / or crosslinking reactions in the next step. In the presence of a photosensitizer (S), the photoactive molecule (S*) directly transfers its energy to the energy accepting molecule, which then generates free radicals by hydrogen abstraction (II) or photolysis (III): This process is called ion photopolymerization.
[0021] In ionic curing, ionic photoinitiators are used to activate functional groups in the oligomer that participate in crosslinking. Photopolymerization is generally a very selective process, and it is important that polymerization occurs only when desired. To this end, anionic or cationic photoinitiators can be incorporated into the neat oligomer in a liquid state, which will initiate polymerization only when exposed to light. Monomers or functional groups used in cationic photopolymerization include compounds such as styrenes, vinyl ethers, N-vinyl carbazoles, lactones, lactams, cyclic ethers, cyclic acetals, and cyclosiloxanes. Most ionic photoinitiators are cationic; anionic photoinitiators are much less studied. Cationic initiators fall into several categories, including onium salts, organometallic compounds, and pyridinium salts. As mentioned earlier, one drawback of photoinitiators used for photopolymerization is that they tend to absorb in the short UV region. Photosensitizers and chromophores absorb longer wavelengths and can be used to excite the photoinitiator via energy transfer. Cation-assisted free radical polymerization is another improvement on this system. In this case, free radicals are generated from another substance in solution and react with the photoinitiator to start the polymerization process. Although there are a large number of compounds activated by cationic photoinitiators, the most commonly used industrially are epoxides, oxetanes, and vinyl ethers. One of the benefits of using a cationic photoinitiator is that after the polymerization reaction has occurred, it is no longer sensitive to oxygen and does not require an inert atmosphere to work well.
[0022] For more than a decade, the preferred method for making PVC plastisols has been to crosslink the product at a suitable temperature. This method involves dissolving the PVC resin in a plasticizer and then reacting it with additives. The recommended temperature for making PVC plastisols is about 180°C, and the preparation time depends on the size of the final product and is estimated to be about 3-15 minutes.
[0023] A disadvantage of this known method is that the energy costs of the processing plant for producing polyvinyl chloride plastisols are high. In addition, harmful components - hydrogen chloride - are released into the environment. In view of the increasing climate problems and the economic and social problems that come with them, all industrial solutions and technologies that aim to significantly reduce energy consumption are particularly important. In addition, with the rising energy prices on the global market, there is a demand for products that reduce the energy costs of industrial plant production. Currently, the process for producing polyvinyl chloride plastisols still consumes a staggering amount of energy costs.
[0024] UV technology reduces energy costs in industrial processing. This method does not require the use of such high temperatures in the preparation process and can optimize the number of personnel required for each unit operation on the production line. Many manufacturers still want to continue using PVC due to its self-extinguishing, non-toxic, acid and alkali resistance, alcohol resistance, gasoline and mineral oil resistance, high mechanical strength and recyclability. Virgin PVC is not reactive enough and is sensitive to photopolymerization without changing its composition.
[0025] Photocrosslinking methods - photopolymerization of PVC plastisols using UV light - are mentioned in some publications.
[0026] EP0275205 discloses a method for producing a louvered plastic film composite structure, comprising the following steps: covering the surface of a first louvered plastic film with a liquid composition, the composition polymerizing to a transparent, hard state after exposure to a selected type of radiation, and firmly bonding to the louvered plastic film after polymerization. Next, contacting the first film with a film of the composition, the first film being transparent to the selected type of radiation, the film being selected to be easily released from the composition after the composition is polymerized; exposing the composite material to sufficient radiation of the selected type to polymerize the composition to a hard state. Thus, a composition in the form of a film - a louvered plastic film, is disclosed, in particular, the film has great flexibility. A simple method for processing a louvered plastic film with a protective coating and a film produced using the method are mentioned. In the method, a solvent-free composition is applied to the louvered plastic film, the composition comprising a mixture of oligomers, monomers and photoinitiators. After exposure to a suitable type of radiation, a layer, preferably a transparent hard layer, is polymerized. The plastic film is placed on the monomer composition, and then the monomer composition is irradiated with polymerizing radiation. Finally, the plastic film is removed, leaving behind a flexible polymer coating that protects the shuttered plastic film. This solution has the disadvantage of requiring the use of reactive, harmful and hazardous monomers.
[0027] FR2574684 discloses a method for producing a polyvinyl chloride wear layer resistant to UV radiation using a formulation containing polyvinyl chloride, a crosslinking agent and a photosensitizer. The method comprises: attaching the formulation in the form of a coating to a substrate under the influence of heat; then crosslinking by ultraviolet light. It discloses a polyvinyl chloride wear layer produced by coating a material containing polyvinyl chloride, a crosslinking agent, a photosensitizer and other possible standard additives on a substrate, the preparation process including thermal gelation and UV radiation crosslinking. The coating is heated to a temperature sufficient for thermal gelation and then photopolymerized by ultraviolet light. All raw materials are first mixed, then degassed, filtered and applied to the substrate to be tested, and then the surface of the material is photocrosslinked by ultraviolet light. The disadvantage of this method is that the temperature during the reaction is very high and it is not possible to reduce costs when processing polyvinyl chloride plastisols at high temperatures.
[0028] EP3677347 discloses a method for improving floor or wall surface coatings, comprising at least the following steps: a) applying a first layer of coating with a thickness of less than 1 mm; b) irradiating the coating with UV light using an LED lamp to pre-crosslink it; c) irradiating the coating with monochromatic radiation using an inert gas; d) irradiating the coating with UV light using a UV lamp to completely crosslink it throughout the thickness. It is mentioned that the coating is applied to a given surface to obtain a fully crosslinked matte coating. It is also mentioned that the type of LED used includes LEDs with a wavelength range of 365-420nm. Conventional UV lamps that do not use LEDs include type A mercury lamps and lamps containing so-called iron, lead, gallium (emitter type, gallium-indium) mixtures. These lamps usually emit a spectrum of 200-400nm. The disadvantage of this method is that there are too many steps to irradiate the product to obtain the desired coating.
[0029] EP0156002 discloses a thermosetting plastisol dispersion composition, which contains at least one powdered acrylonitrile-butadiene-styrene (ABS) copolymer, which is insoluble in a reactive plasticizer at room temperature and plasticizable at or above the melting point; in addition, it also contains a liquid reactive plasticizer selected from the group consisting of: (a) at least one epoxy resin having an average of more than one epoxy group per molecule, (b) at least one liquid monomer, oligomer or prepolymer, characterized by containing at least one ethylenically unsaturated group and being able to dissolve ABS at its melting point. It also mentions a mixture of (a) and (b); and an effective amount of a thermal initiator or a photoinitiator to the plasticizer in the composition. The melted plastisol dispersion can form a thermosetting sealant, coating or adhesive after a crosslinking reaction. The disadvantage of this method is that it requires the use of reactive monomers and oligomers, high temperature processing of the product, and the inability to reduce costs when the product is processed at high temperature.
[0030] US4929171 discloses a method for coating a polyvinyl chloride composite plastisol coating on a metal plate, comprising: coating a polyvinyl chloride composite plastisol coating on a metal plate, the polyvinyl chloride composite plastisol comprising 100 parts of polyvinyl chloride powder, wherein, by weight percentage, more than 95% of the particles have a particle size in the range of 0.5-40 μm, 20% to 60% of the particles have a particle size in the range of 0.5-5 μm, 35% to 75% of the particles have a particle size in the range of 0.5-40 μm, and 5% to 60% of the particles are composed of acrylic monomers, acrylic oligomers or mixtures thereof, the monomers or oligomers having at least one functional group and at least one initiator or photoinitiator for thermal curing, thereby forming a polyvinyl chloride coated composite sheet. Subsequently, the composite metal plate coated with polyvinyl chloride is heated at a temperature of 150°C to 250°C to obtain a composite metal plate coated with polyvinyl chloride. The disadvantages of this method are that it requires the use of reactive monomers and oligomers, high temperature processing of the product, and the inability to reduce costs when processing the product at high temperatures.
[0031] Disadvantages of known methods and compositions for obtaining polyvinyl chloride plastisols by photocrosslinking include the use of reactive, harmful and hazardous monomers, oligomers, multi-step production processes, high temperature treatments and the inability to reduce costs when subjecting the products to high temperature processing. Summary of the invention
[0032] The object of the present invention is to develop a solution which is both energy-saving and does not have the above-mentioned disadvantages, namely a method for preparing PVC plastisols using only UV light, without the use of reactive hazardous raw materials or high temperatures.
[0033] The present invention is a new formula for processing polyvinyl chloride plastisols, which obtains crosslinked polyvinyl chloride plastisols by adding a unique composition component, which allows photopolymerization reaction in a specific ultraviolet light range, a gelling agent and a melt plasticizer and a polymer, or other polymers added in the variant of the present invention that do not initiate the formation of PVC polymers or toxic substances (hydrochloric acid gas-hydrochloride) in the polymer, thereby replacing the current high-energy consumption and toxic polyvinyl chloride plastisols. This new plastisol composition does not require high-temperature processing, only ultraviolet light, that is, ordinary ultraviolet lamps or LED lamps. In addition, since the processing technology of the plastisol is changed from high temperature to ultraviolet light, high temperatures are not reached during the processing, so there is no need to cool the finished product. As a result, the plastisol produced according to the present invention is much less harmful to health and more environmentally friendly.
[0034] Plastisols do not develop severe pseudoplastic fluid viscosity during their shelf life, but instead maintain a long-term stable creamy Newtonian fluid viscosity and do not increase viscosity rapidly.
[0035] The composition formulation for obtaining a photocrosslinked plastisol according to the present invention comprises the following three basic components: PVC virgin resin or PVC & AC copolymer or PVC & PVAC copolymer, such as the copolymers produced by Vestolit or Vinnolit; a plasticizer mixture, namely the known phosphorus-containing plasticizer - diisodecyl phthalate; and a photoinitiator, namely 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0036] Specifically, the three basic ingredients are: a) PVC polyvinyl chloride polymer-resin, i.e. the original form of polyvinyl chloride, or another polyvinyl chloride is used to replace the original form of polyvinyl chloride, referred to as the second polyvinyl chloride copolymer in this specification, which can be vinyl acetate PVC & AC or polyvinyl chloride-acrylic acid copolymer PVC & PVAC, b) Mixed plasticizers: Two plasticizers: the first contains commercially available phosphorus and the second is diisononyl phthalate.
[0037] c) A photoinitiator with a wavelength between 365-400 nm, preferably below 395 nm, namely, a 2,4,6-trimethylbenzoyl-diphenylphosphine oxide compound.
[0038] The weight ratio of the plasticizer mixture to the polyvinyl chloride polymer-resin or any of the above copolymers is preferably 65:100, and the amount of photoinitiator is 5 to 20 phr (dosage required per 100 parts of resin) relative to 100 parts of polyvinyl chloride resin or copolymer.
[0039] The quantitative content of the plasticizer mixture in the formula is as follows: 35.14% to 38.24% of the total weight of the abc mixture, of which, by weight percentage, the first plasticizer containing commercially available phosphorus accounts for 8.11% to 8.82% of the total formula; the second plasticizer diisononyl phthalate accounts for 27.03% to 29.41% of the total formula.
[0040] The quantitative content of the total polyvinyl chloride polymer or any of the above copolymers in the formula is as follows: 54.05% to 58.82% of the total abc mixture.
[0041] The quantitative content of the photoinitiator in the formulation is as follows, by weight percentage: 2.94% to 10.81% of the abc mixture.
[0042] The content of the polyvinyl chloride polymer or copolymer is selected according to the content of the above-mentioned other ingredients. The composition for obtaining plastisol and photo-crosslinked polyvinyl chloride plastisol may also contain at least one known ingredient selected from the group consisting of wetting agent, dispersant, crosslinking agent, filler, foaming agent, rheology modifier, thixotropic agent, lubricant, antistatic agent, heat stabilizer, dye, flame retardant, foaming agent, viscosity reducer, diluent and ultraviolet absorber.
[0043] The plastisol composition applied to the substrate is exposed to ultraviolet radiation within the following wavelength ranges to cure the coating applied to the target material: at 20 0 C to 60 0 C temperature, wavelength 365-400nm, preferably 365-395nm.
[0044] The method for obtaining a photo-crosslinked polyvinyl chloride plastisol using virgin polyvinyl chloride and forming a coating on any surface using the composition according to the present invention comprises the following steps: a) obtaining the above-mentioned plastisol composition, which is obtained by mixing a ground photoinitiator with a phosphorus-containing plasticizer, wherein the photoinitiator is preferably a crushed photoinitiator, and its weight accounts for 2.94% to 10.81% of the total formula, and the weight of the phosphorus-containing plasticizer accounts for 8.11% to 8.82% of the total formula; firstly mixing the formula a at room temperature for about 2 minutes, and then adding 54.05% to 58.82% of the weight of the virgin polyvinyl chloride resin copolymer accounting for 54.05% to 58.82% of the total formula, and mixing for about 5 minutes at room temperature; then, adding 27.03% to 29.41% of the main plasticizer diisodecyl phthalate accounting for 27.03% to 29.41% of the total formula into the formula, and mixing for about 5 minutes; b) applying the plastisol composition to the substrate to be coated, which substrate is preferably glass or steel or polyester or aluminum; and c) exposing the plastisol composition coated on the substrate to ultraviolet radiation within the following wavelength range: 0 C to 60 0 The composition is cured at a temperature of 365-400 nm (preferably 365-395 nm) for a period of time, preferably 6 seconds, to achieve complete surface crosslinking, preferably 6 seconds, to avoid surface burning and dissociation. Too long a crosslinking time (for non-ground / non-crushed photoinitiator, more than 1 minute; for ground / crushed photoinitiator, more than 6 seconds) will result in surface burning and dissociation. On the other hand, too short a crosslinking time, for example, less than 6 seconds, is insufficient to obtain a crosslinked hard coating.
[0045] In another variant of the method for obtaining a photo-crosslinked polyvinyl chloride plastisol and using the above composition to form a coating on any surface according to the present invention, another above-mentioned copolymer is used instead of the polyvinyl chloride plastisol resin, that is, polyvinyl chloride-vinyl acetate copolymer PVC & AC, comprising the following steps: a) obtaining the above-mentioned plastisol composition, which is obtained by mixing a ground photoinitiator with a phosphorus-containing plasticizer, wherein the photoinitiator is preferably a crushed photoinitiator, and its weight accounts for 2.94% to 10.81% of the total formula, and the weight of the phosphorus-containing plasticizer accounts for 8.11% to 8.82% of the total formula; at room temperature, first mixing formula a for about 2 minutes, and then adding 54.05% to 58.82% of PVC & AC copolymer resin, which accounts for 54.05% to 58.82% of the total formula, and mixing for about 5 minutes at room temperature; then, adding 27.03% to 29.41% of the main plasticizer diisodecyl phthalate, which accounts for 27.03% to 29.41% of the total formula, into the formula and mixing for about 5 minutes; b) applying the plastisol composition to the substrate to be coated, which substrate is preferably glass or steel or polyester or aluminum; and c) exposing the plastisol composition coated on the substrate to ultraviolet radiation within the following wavelength range: 0 C to 60 0 The composition is cured at a temperature of 365-400 nm (preferably 365-395 nm) for a period of time, preferably 6 seconds, to achieve complete surface crosslinking, preferably 6 seconds, to avoid surface burning and dissociation. Too long a crosslinking time (for non-ground / non-crushed photoinitiator, more than 1 minute; for ground / crushed photoinitiator, more than 6 seconds) will result in surface burning and dissociation. On the other hand, too short a crosslinking time, for example, less than 6 seconds, is insufficient to obtain a crosslinked hard coating.
[0046] In another variant of the method for obtaining a photo-crosslinked polyvinyl chloride plastisol and using the above composition to form a coating on any surface according to the present invention, another above-mentioned copolymer is used instead of the polyvinyl chloride plastisol, namely polyvinyl chloride-vinyl acetate copolymer PVC & PVAC, comprising the following steps: a) obtaining the above-mentioned plastisol composition, which is obtained by mixing a ground photoinitiator with a phosphorus-containing plasticizer, wherein the photoinitiator is preferably a crushed photoinitiator, and its weight accounts for 2.94% to 10.81% of the total formula, and the weight of the phosphorus-containing plasticizer accounts for 8.11% to 8.82% of the total formula; firstly mixing the formula a at room temperature for about 2 minutes, and then adding 54.05% to 58.82% of the PVC & PVAC copolymer resin by weight accounting for the total formula, and mixing for about 5 minutes at room temperature; then, adding 27.03% to 29.41% of the main plasticizer diisodecyl phthalate by weight accounting for the total formula into the formula, and mixing for about 5 minutes; b) applying the plastisol composition to the substrate to be coated, which substrate is preferably glass or steel or polyester or aluminum; and c) exposing the plastisol composition coated on the substrate to ultraviolet radiation within the following wavelength range: 0 C to 60 0 The composition is cured at a temperature of 365-400 nm (preferably 365-395 nm) for a period of time, preferably 6 seconds, to achieve complete surface crosslinking, preferably 6 seconds, to avoid surface burning and dissociation. Too long a crosslinking time (for non-ground / non-crushed photoinitiator, more than 1 minute; for ground / crushed photoinitiator, more than 6 seconds) will result in surface burning and dissociation. On the other hand, too short a crosslinking time, for example, less than 6 seconds, is insufficient to obtain a crosslinked hard coating.
[0047] 4. Advantages of the present invention UV technology is leading the revolution in the PVC processing industry. The invention can be used in today's energy-intensive production plants, i.e. large industrial production lines that require high temperatures and long processing times for PVC plastisols, such as plants producing wallpaper, artificial leather, and PVC flooring.
[0048] The present invention can reduce pollutants discharged into the environment, reduce unused heat energy generated during the heating process of polyvinyl chloride plastisol, and shorten production time. For example, in the production of an inflatable castle, a layer of 0.4 mm polyvinyl chloride plastisol is covered on a 1 m long polyester fabric, and a layer of 0.4 mm polyvinyl chloride plastisol is coated on each 1 m long polyester fabric. 2 The processing time is about 9 minutes, while through UV irradiation, the product can be completely cross-linked in just 6 seconds.
[0049] The benefits of implementing this project also include reducing electricity demand, thus serving the promotion of low-carbon climate policies and energy emission reduction policies. Today, plasticized polyvinyl chloride is still used in large quantities in many industries, such as the wallpaper industry, the wider automotive industry, floor coverings, coatings and other industries. Its processing is very energy-intensive, which poses a challenge to the normal operation of enterprises with the continuous increase in energy costs and the pressure to adopt green solutions. UV technology can significantly reduce costs.
[0050] From a practical point of view, once the present invention is put into use, manufacturers can reduce process costs related to energy costs when processing polyvinyl chloride, as well as reduce the labor costs required to run the process, compared to current production methods.
[0051] This is an opportunity for entrepreneurs and the Polish economy to realize innovative projects that will allow us to stand out on the international stage. In addition, it will be possible to save processing costs without changing the raw materials currently used. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Hereinafter, the present invention will be described in more detail in conjunction with the embodiments of the present invention and the accompanying drawings. Figure 1 The UV lamp used for the test is shown, and its operating wavelength range is 365-400nm, wherein the cross-linking conditions at wavelengths of 365 and 395nm are shown; and Figure 2 The entire advertising element is shown - a logo made of polyvinyl chloride plastisol and treated with UV technology.
[0053] These examples demonstrate that the plastisol is cured under ultraviolet light of a specific wavelength, and the obtained marking results are as follows Figure 2 shown. DETAILED DESCRIPTION
[0054] Example 1 - Research of the Invention - Introduction Photocrosslinking The product, polyvinyl chloride plastisol, is processed under industrial conditions using electromagnetic radiation with a wavelength of 365-395nm UV light. Competitive commercially available UV lamps are used instead of the current method of processing PVC plastisols at temperatures of approximately 180°C. The photoinitiator used in the study is active in the wavelength range of 365-400nm.
[0055] The effect of various active photoinitiators in the wavelength range of 365-400nm was tested using a UV lamp. For this purpose, PVC plastisol samples based on virgin PVC emulsions with phthalate plasticizers were prepared and different photoinitiators were added according to the wavelength of 365-400nm (preferably 395nm). Based on the results of the study, the most effective photoinitiator was selected, namely 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0056] Plasticizers with epoxy groups, sebacates, citrates, polymeric plasticizers with different degrees of polymer chain branching were tested. Each sample was tested for sensitivity to photopolymerization using a UV lamp in the wavelength range of 365-395 nm as described above. Based on the results of the study, two effective plasticizers were selected: the first containing commercially available phosphorus and the second diisononyl phthalate.
[0057] The photopolymerization efficiency of polyvinyl chloride resin, virgin polyvinyl chloride or polyvinyl chloride-vinyl acetate copolymer or polyvinyl chloride-acrylic acid copolymer system was compared. The photopolymerization sensitivity of the system is the same regardless of the polyvinyl chloride resin used or the copolymer selected. From an economic point of view, the use of virgin polyvinyl chloride resin is recommended.
[0058] It was tested whether the introduction of reactive hydroxyl groups or polyhydroxyl groups into virgin polyvinyl chloride resin products could achieve photopolymerization.
[0059] All samples were tested at different UV irradiances and the time required for the PVC plastisol to start crosslinking was examined, as well as whether the crosslinking occurred on the surface or inside the product. The products were tested on various substrates, such as thin aluminum sheets, paper, polyester fabric, and aluminum molds.
[0060] During the test, polyvinyl chloride plastisol samples were prepared with the following mixtures and contents, and the photopolymerization sensitivity of the samples was tested under 365-395 nm wavelength UV light.
[0061] Four photoinitiator samples were prepared and plasticizer diisodecyl phthalate, a phosphorus-containing plasticizer, was added.
[0062] Then PVC resin was added to the samples along with a photoinitiator and plasticizer: virgin resin in the first sample (Table 1), PVC copolymer with acrylic acid (ACR acrylamide concentration between 10-40%) in the second sample (Table 2), and PVC copolymer with vinyl acetate (constant K value between 60-80) in the third sample (Table 3). Regardless of the resin used, the samples showed the same crosslinking sensitivity under UV irradiation.
[0063] The effect of the photoinitiator particle size on its efficiency in the system was tested. To obtain smaller particles, the photoinitiator was crushed in a mortar and pestle, and plastisol samples were made with both crushed and un-crushed photoinitiators. The tests showed that the photoinitiator with a smaller particle size (crushed) was more efficient, meaning that less photoinitiator could be used and photopolymerization occurred after only 6 seconds of exposure on the coating, compared to 1 minute with the un-crushed photoinitiator. This method measures the crosslinking time by crushing the photoinitiator.
[0064] The crosslinking time according to the invention is determined on this basis.
[0065] All samples were crosslinked on the following substrates: Steel substrate: irradiate plastisol coating for 6 seconds Glass substrate: irradiate plastisol coating for 6 seconds Polyester substrate: irradiate the plastisol coating for 6 seconds. Any longer than 6 seconds will cause the fabric to burn and will not adhere to the polyester fabric. Aluminum substrate: irradiate the plastisol coating for 6 seconds.
[0066] The plastisol surface was irradiated for different times to determine the optimal time required for crosslinking the product using UV light, and it was found that the PVC plastisol surface cured after 6 seconds of irradiation. A thin layer of PVC plastisol (about 1 mm) was applied to steel, polyester fabric, glass or paper substrates, and the substrate surface was then exposed to UV light to check the occurrence of photocrosslinking reaction. The plastisol was irradiated for different lengths of time: 6 seconds, 10 seconds, 15 seconds, 20 seconds, 40 seconds, 60 seconds. The tests showed that the PVC plastisol surface cured when the coating was irradiated for 6 seconds, regardless of the substrate used. In addition, on glass, paper and polyester fabric substrates, crosslinking of the product on the substrate was observed after 6 seconds of irradiation, while on metal substrates, the plastisol required about 60 seconds for crosslinking to occur.
[0067] Example 2 The table gives examples of proven formulations according to the invention, listing the quantitative and qualitative composition of the base materials used in the products. Table 1: PVCUV / 23 / 1 - proper nouns
[0068] Table 2: PVCUV / 23 / 1A - proper nouns
[0069] Table 3: PVCUV / 23 / 2 - proper nouns
[0070] Table 4: PVCUV / 23 / 2A - Proper Nouns
[0071] Table 5: PVCUV / 23 / 3 - proper nouns
[0072] Table 6: PVCUV / 23 / 3A - proper nouns
[0073] Methods for obtaining variants of the invention a) Table 1 The method for obtaining the photo-crosslinked polyvinyl chloride plastisol shown in Table 1 and forming a coating on any surface using the composition according to the present invention comprises the following steps: a) obtaining a sol composition, wherein the composition is obtained by the following steps: adding a ground photoinitiator, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, as described in Example 1, to a phosphorus-containing plasticizer in an amount shown in Table 1 and mixing for about 2 minutes at room temperature, then adding the mixture to a virgin polyvinyl chloride polymer in an amount shown in Table 1 and mixing for 5 minutes at room temperature; then, adding a primary plasticizer, diisodecyl phthalate, in a ratio given in Table 1, to the obtained mixture and mixing for about 2 minutes, and stirring at a speed of 600 rpm for 2 minutes on a mechanical stirrer with a shear stirring head; degassing the prepared sample in a vacuum chamber until the surface is smooth; after degassing, filtering the sample with a 100-700 μm sieve; b) Applying the plastisol composition to the substrate to be coated, such as a glass or aluminum plate, Q-type panel QD-2-3.5: Panel quality parameters: smooth, glossy finish; Width: 51 mm; Length: 89 mm; Thickness: 0.51 mm; Q-type panel contains manganese and phosphorus, with a carbon content of up to 0.15%; or a milled aluminum structure or polyester fabric for an inflatable castle.
[0074] c) Use Figure 1 The UV lamp shown in the figure is 20 0 The plastisol composition coated on the substrate was irradiated at a temperature of 1000 ° C., with a wavelength range of 365-395 nm, for 6 seconds to cure the composition. In this embodiment, too long an irradiation time would result in surface burning and dissociation.
[0075] The product can be irradiated by ultraviolet light technology, ultraviolet light of a specific wavelength, Fourier transform infrared spectroscopy, gas chromatography, spectrophotometry, nuclear magnetic resonance, DSC (in this embodiment, ultraviolet light of 365-395 nm wavelength) and the like.
[0076] Similarly, for plastisol coatings on the same material at 60 0 The crosslinking behavior under irradiation with UV light at a wavelength of 365-395 nm at a temperature of 1000 ° C was estimated to ensure that the composition would cure in 6 seconds.
[0077] The effect of exposure at both temperatures is evaluated by touching the surface of the exposed samples. If the surface is cured, it is considered that the technology is working satisfactorily. Other products have been reviewed on the production line. Figure 2 The product advertising element logo produced using ultraviolet light technology is shown. Figure 2 As shown, the plastisol is cured under ultraviolet light of a specific wavelength. As a result, the logo shown in the figure is obtained.
[0078] Example 3 Table 2 Method description The same approach as in Table 1 is used, but with different parameters.
[0079] The second method for obtaining the photo-crosslinked polyvinyl chloride plastisol shown in Table 2 and using the above composition to form a coating on any surface according to the present invention comprises the following steps a) obtaining a plastisol composition, wherein the composition is obtained by the following steps: adding a ground photoinitiator, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, as described in Example 1, to a phosphorus-containing plasticizer in an amount shown in Table 2 and mixing for 2 minutes at room temperature, then adding the mixture to a virgin polyvinyl chloride polymer in an amount shown in Table 2 and mixing for 5 minutes at room temperature; then, adding a primary plasticizer, diisodecyl phthalate, in a ratio given in Table 2, to the obtained mixture and mixing for about 2 minutes, and stirring for 2 minutes on a mechanical stirrer with a shear stirring head at a speed of 600 rpm; degassing the prepared sample in a vacuum chamber until the surface is smooth; after degassing, filtering the sample with a 100-700 μm sieve; b) Applying the plastisol composition to the substrate to be coated, such as a glass or aluminum plate, Q-type panel QD-2-3.5: Panel quality parameters: smooth, glossy finish; Width: 51 mm; Length: 89 mm; Thickness: 0.51 mm; Q-type panel contains manganese and phosphorus, with a carbon content of up to 0.15%; or a milled aluminum structure or polyester fabric for an inflatable castle.
[0080] c) Use Figure 1 The UV lamp shown in the figure is 20 0 The plastisol composition coated on the substrate is irradiated at a temperature of 1000 ° C, with a wavelength range of 365-395 nm, for 6 seconds to cure the composition. Excessive irradiation time will cause surface burning and dissociation.
[0081] The exposure effect is evaluated by touching the surface of the exposed sample. If the surface is cured, it can be considered that the technology is working satisfactorily. Other products have been inspected on the production line. Figure 2 Shown is a product advertising element logo made using ultraviolet light technology.
[0082] The product can be irradiated by ultraviolet light technology, ultraviolet light of a specific wavelength, Fourier transform infrared spectroscopy, gas chromatography, spectrophotometry, nuclear magnetic resonance, DSC (in this embodiment, ultraviolet light of 365-395 nm wavelength) and the like.
[0083] Similarly, for plastisol coatings on the same material at 60 0 The crosslinking behavior under irradiation with UV light at a wavelength of 365-395 nm at a temperature of 1000 ° C was estimated to ensure that the composition would cure in 6 seconds.
[0084] The evaluation of the lighting effect at these two temperatures is similar to the above embodiment - (c) and (d) in the method description of Table 1 Figure 2 described.
[0085] Example 4 - Table 3 Method Description The third method for obtaining the photo-crosslinked polyvinyl chloride plastisol shown in Table 3 and using the above composition to form a coating on any surface according to the present invention comprises the following steps: a) obtaining a plastisol composition, wherein the composition is obtained by the following steps: adding a ground photoinitiator, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, as described in Table 3, to a phosphorus-containing plasticizer in an amount shown in Table 3 at room temperature and mixing for about 2 minutes, then adding the mixture to a PVC & AC polymer in an amount shown in Table 3 at room temperature and mixing for 5 minutes; then, adding a primary plasticizer, diisodecyl phthalate, in a ratio given in Table 3, to the obtained mixture and mixing for about 2 minutes, and stirring for 2 minutes on a mechanical stirrer with a shear stirring head at a speed of 600 rpm; degassing the prepared sample in a vacuum chamber until the surface is smooth; after degassing, filtering the sample with a 100-700 μm sieve; b) Applying the plastisol composition to the substrate to be coated, such as a glass or aluminum plate, Q-type panel QD-2-3.5: Panel quality parameters: smooth, glossy finish; Width: 51 mm; Length: 89 mm; Thickness: 0.51 mm; Q-type panel contains manganese and phosphorus, with a carbon content of up to 0.15%; or a milled aluminum structure or polyester fabric for an inflatable castle.
[0086] c) Use Figure 1 The UV lamp shown in the figure is 20 0 The plastisol composition coated on the substrate is irradiated at a temperature of 1000 ° C, with a wavelength range of 365-395 nm, for 6 seconds to cure the composition. Excessive irradiation time will cause surface burning and dissociation.
[0087] The exposure effect is evaluated by touching the surface of the exposed sample. If the surface is cured, it can be considered that the technology is working satisfactorily. Other products have been inspected on the production line. Figure 2 Shown is a product advertising element logo made using ultraviolet light technology.
[0088] The product can be irradiated by ultraviolet light technology, ultraviolet light of a specific wavelength, Fourier transform infrared spectroscopy, gas chromatography, spectrophotometry, nuclear magnetic resonance, DSC (in this embodiment, ultraviolet light of 365-395 nm wavelength) and the like.
[0089] Similarly, for plastisol coatings on the same material at 60 0The crosslinking behavior under irradiation with UV light at a wavelength of 365-395 nm at a temperature of 1000 ° C was estimated to ensure that the composition would cure in 6 seconds.
[0090] The evaluation of the lighting effect at these two temperatures is similar to the above embodiment - (c) and (d) in the method description of Table 1 Figure 2 described.
[0091] Example 5 - Table 4 Method Description The fourth method for obtaining the photo-crosslinked polyvinyl chloride plastisol shown in Table 4 and forming a coating on any surface using the above composition according to the present invention comprises the following steps: a) obtaining a plastisol composition, wherein the composition is obtained by the following steps: adding a ground photoinitiator, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, as described in Table 4, to a phosphorus-containing plasticizer in an amount shown in Table 4 at room temperature and mixing for about 2 minutes, then adding the mixture to a PVC & AC polymer in an amount shown in Table 4 at room temperature and mixing for 5 minutes; then, adding a primary plasticizer, diisodecyl phthalate, in a ratio given in Table 4, to the obtained mixture and mixing for about 2 minutes, and stirring for 2 minutes on a mechanical stirrer with a shear stirring head at a speed of 600 rpm; degassing the prepared sample in a vacuum chamber until the surface is smooth; after degassing, filtering the sample with a 100-700 μm sieve; b) Applying the plastisol composition to the substrate to be coated, such as a glass or aluminum plate, Q-type panel QD-2-3.5: Panel quality parameters: smooth, glossy finish; Width: 51 mm; Length: 89 mm; Thickness: 0.51 mm; Q-type panel contains manganese and phosphorus, with a carbon content of up to 0.15%; or a milled aluminum structure or polyester fabric for an inflatable castle.
[0092] c) Use Figure 1 The UV lamp shown in the figure is 20 0 The plastisol composition coated on the substrate is irradiated at a temperature of 1000 ° C, with a wavelength range of 365-395 nm, for 6 seconds to cure the composition. Excessive irradiation time will cause surface burning and dissociation.
[0093] The exposure effect is evaluated by touching the surface of the exposed sample. If the surface is cured, it can be considered that the technology is working satisfactorily. Other products have been inspected on the production line. Figure 2 Shown is a product advertising element logo made using ultraviolet light technology.
[0094] The product can be irradiated by ultraviolet light technology, ultraviolet light of a specific wavelength, Fourier transform infrared spectroscopy, gas chromatography, spectrophotometry, nuclear magnetic resonance, DSC (in this embodiment, ultraviolet light of 365-395 nm wavelength) and the like.
[0095] Similarly, for plastisol coatings on the same material at 60 0 The crosslinking behavior under irradiation with UV light at a wavelength of 365-395 nm at a temperature of 1000 ° C was estimated to ensure that the composition would cure in 6 seconds.
[0096] The evaluation of the lighting effect at these two temperatures is similar to that described in (c) of the method description of Table 1 in Example 2 above.
[0097] Example 6 - Table 5 Method Description The fifth method of obtaining the photo-crosslinked polyvinyl chloride plastisol shown in Table 5 and using the above composition to form a coating on any surface according to the present invention comprises the following steps: a) obtaining a plastisol composition, wherein the composition is obtained by the following steps: adding a ground photoinitiator, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, as described in Table 5, to a phosphorus-containing plasticizer in an amount shown in Table 5 at room temperature and mixing for about 2 minutes, then adding the mixture to a PVC & PVAC polymer in an amount shown in Table 5 at room temperature and mixing for 5 minutes; then, adding a primary plasticizer, diisodecyl phthalate, in a ratio given in Table 5, to the obtained mixture and mixing for about 2 minutes, and stirring for 2 minutes on a mechanical stirrer with a shear stirring head at a speed of 600 rpm; degassing the prepared sample in a vacuum chamber until the surface is smooth; after degassing, filtering the sample with a 100-700 μm sieve; b) Applying the plastisol composition to the substrate to be coated, such as a glass or aluminum plate, Q-type panel QD-2-3.5: Panel quality parameters: smooth, glossy finish; Width: 51 mm; Length: 89 mm; Thickness: 0.51 mm; Q-type panel contains manganese and phosphorus, with a carbon content of up to 0.15%; or a milled aluminum structure or polyester fabric for an inflatable castle.
[0098] c) Use Figure 1 The UV lamp shown in the figure is 20 0 The plastisol composition coated on the substrate is irradiated at a temperature of 1000 ° C, with a wavelength range of 365-395 nm, for 6 seconds to cure the composition. Excessive irradiation time will cause surface burning and dissociation.
[0099] The exposure effect is evaluated by touching the surface of the exposed sample. If the surface is cured, it can be considered that the technology is working satisfactorily. Other products have been inspected on the production line. Figure 2 Shown is a product advertising element logo made using ultraviolet light technology.
[0100] The product can be irradiated by ultraviolet light technology, ultraviolet light of a specific wavelength, Fourier transform infrared spectroscopy, gas chromatography, spectrophotometry, nuclear magnetic resonance, DSC (in this embodiment, ultraviolet light of 365-395 nm wavelength) and the like.
[0101] Similarly, for plastisol coatings on the same material at 60 0 The crosslinking behavior under irradiation with UV light at a wavelength of 365-395 nm at a temperature of 1000 ° C was estimated to ensure that the composition would cure in 6 seconds.
[0102] The evaluation of the lighting effect at these two temperatures is similar to that described in c) in the method description of Table 1 in the above example.
[0103] The evaluation of the exposure effect is similar to that described in the above example - c) in the method description of Table 1.
[0104] Example 7 - Table 6 Method Description The sixth method for obtaining the photo-crosslinked polyvinyl chloride plastisol shown in Table 6 and forming a coating on any surface using the above composition according to the present invention comprises the following steps: a) obtaining a plastisol composition, wherein the composition is obtained by the following steps: adding a ground photoinitiator, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, as described in Table 6, to a phosphorus-containing plasticizer in an amount shown in Table 6 and mixing for about 2 minutes at room temperature, and then adding the mixture to a PVC&PVAC polymer in an amount shown in Table 6 and mixing for 5 minutes at room temperature; then, adding a primary plasticizer, diisodecyl phthalate, in a ratio given in Table 6, to the obtained mixture and mixing for about 2 minutes, and stirring for 2 minutes on a mechanical stirrer with a shear stirring head at a speed of 600 rpm; degassing the prepared sample in a vacuum chamber until the surface is smooth; after degassing, filtering the sample with a 100-700 μm sieve; b) Applying the plastisol composition to the substrate to be coated, such as a glass or aluminum plate, Q-type panel QD-2-3.5: Panel quality parameters: smooth, glossy finish; Width: 51 mm; Length: 89 mm; Thickness: 0.51 mm; Q-type panel contains manganese and phosphorus, with a carbon content of up to 0.15%; or a milled aluminum structure or polyester fabric for an inflatable castle.
[0105] c) Use Figure 1 The UV lamp shown in the figure is 20 0 The plastisol composition coated on the substrate is irradiated at a temperature of 1000 ° C, with a wavelength range of 365-395 nm, for 6 seconds to cure the composition. Excessive irradiation time will cause surface burning and dissociation.
[0106] The exposure effect is evaluated by touching the surface of the exposed sample. If the surface is cured, it can be considered that the technology is working satisfactorily. Other products have been inspected on the production line. Figure 2 Shown is a product advertising element logo made using ultraviolet light technology.
[0107] The product can be irradiated by ultraviolet light technology, ultraviolet light of a specific wavelength, Fourier transform infrared spectroscopy, gas chromatography, spectrophotometry, nuclear magnetic resonance, DSC (in this embodiment, ultraviolet light of 365-395 nm wavelength) and the like.
[0108] Similarly, for plastisol coatings on the same material at 60 0 The crosslinking behavior under irradiation with UV light at a wavelength of 365-395 nm at a temperature of 1000 ° C was estimated to ensure that the composition would cure in 6 seconds.
[0109] The evaluation of the lighting effect at these two temperatures is similar to that described in (c) of the method description of Table 1 in the above embodiment.
Claims
1. A formulation for obtaining a photocrosslinked plastisol comprising a polyvinyl chloride (PVC) polymer and at least one plasticizer, characterized in that The formula comprises virgin polyvinyl chloride or vinyl acetate copolymer PVC&AC or vinyl chloride and acrylic acid copolymer PVC&PVAC in resin form, a plasticizer mixture comprising a phosphorus-containing plasticizer and diisononyl phthalate, and a photoinitiator with a wavelength range of 365-400nm, preferably 395nm, wherein the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, wherein, by weight percentage, the plasticizer mixture accounts for 35.14% to 38.24% of the formula, the polyvinyl chloride polymer accounts for 54.05% to 58.82% of the formula, and the photoinitiator accounts for 2.94% to 10.81% of the formula.
2. The formulation according to claim 1, characterized in that By weight percentage, the phosphorus-containing plasticizer accounts for 8.11% to 8.82% of the formula, and the diisononyl phthalate accounts for 27.03% to 29.41% of the formula.
3. The formulation according to claim 1, characterized in that The weight ratio of the plasticizer mixture to the polyvinyl chloride polymer is from about 0.5:1 to about 1:1; Furthermore, relative to 100 parts of polyvinyl chloride, the amount of the photoinitiator is 5 to 20 phr (the amount required for every 100 parts of resin).
4. The method for obtaining a photo-crosslinked polyvinyl chloride plastisol using virgin polyvinyl chloride and forming a coating on any surface using the composition according to the present invention comprises the following steps.
5. A method for obtaining a photo-crosslinked plastisol formulation comprising a polyvinyl chloride (PVC) polymer and at least one plasticizer, characterized in that The method comprises: mixing a photoinitiator with a phosphorus-containing plasticizer, wherein the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, preferably in a crushed form, with a wavelength range of 365-400nm, preferably 395nm, accounting for 2.94% to 10.81% of the formula by weight percentage, and the phosphorus-containing plasticizer accounts for 8.11% to 8.82% of the formula by weight percentage; adding polyvinyl chloride in its native form, i.e., resin or PVC&AC vinyl acetate copolymer or PVC&PVAC polyvinyl chloride-acrylic acid copolymer, accounting for 54.05% to 58.82% of the formula by weight percentage; and adding a plasticizer diisononyl phthalate to the obtained mixture, the plasticizer accounting for 27.03% to 29.41% of the formula by weight percentage.
6. The method according to claim 5, characterized in that The obtained formulation is applied on any substrate, preferably glass or steel or polyester or aluminum substrate, and exposed to UV radiation in the wavelength range: 365-400 nm, preferably 365-395 nm, at a temperature of 20°C to 60°C, until the combination cures.
7. The method according to claims 5-6, characterized in that: In the process of photo-crosslinking the surface of the plastisol formulation to cure it, in order to avoid burning and dissociation of the surface, when the photoinitiator is applied, the crosslinking time is up to about 6 seconds; when the photoinitiator is not applied, the crosslinking time is up to about 1 minute.
Citation Information
Patent Citations
Reactive plastisol dispersion
EP0156002A2
Method for making a flexible louvered plastic film with protective coatings and film produced thereby
EP0275205A2
Composite polyvinylchloride plastisol coating and method of applying it to a metal sheet
US4929171A